2018
DOI: 10.18488/journal.1.2018.88.603.613
|View full text |Cite
|
Sign up to set email alerts
|

Types of Employee Participation in Decision Making (PDM) amongst the Middle Management in the Malaysian Public Sector

Abstract: Over the years, there has been tremendous growth of interest in employee participation in decision-making or PDM from a various discipline of studies such as industrial relations, management, human resource management (HRM), organisational behaviour, and political economy. Therefore, this paper aimed to identify the types of employee"s direct participation particularly on delegative, consultative and non-participation in decision-making at the middle management in the six selected ministries in Putrajaya, Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In terms of political influence, a study by Shaed et al [5] reveals that the decision making of public organizations gives the power to decide to political forces, placing political concerns above economic issues. In addition, it states that wide levels of decision and bureaucracy exist, which makes it a slower and more time-consuming process.…”
Section: Meso Level: Ownership and Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In terms of political influence, a study by Shaed et al [5] reveals that the decision making of public organizations gives the power to decide to political forces, placing political concerns above economic issues. In addition, it states that wide levels of decision and bureaucracy exist, which makes it a slower and more time-consuming process.…”
Section: Meso Level: Ownership and Sizementioning
confidence: 99%
“…Talib and Rahman [4] consider that PDM is concerned with how employers allow their employees to be involved in organizational decision making. Previous studies have focused on a type of PDM, such as consultative or delegative [5], direct or indirect [6,7], or active or passive [8], but only a few are based on the matter of decision making [9][10][11]. This paper aims to shed light on this issue, analyzing PDM from two different perspectives: operational, when employees decide on direct tasks (i.e., how to organize their work, time, and speed and how to set their own schedules and goals) [12], and organizational, in which they have a decision on organizational matters (i.e., vision, mission, organizational goals) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Employee involvement has been used in the literature interchangeably with employee participation, job involvement, job engagement, employee engagement, and employee voice (Appelbaum, Louis, Makarenko, Saluja, Meleshko & Kulbashian, 2013;Shaed, Zainol, Yusof & Bahrin, 2018). According to Nachiket (2014) employees' involvement is a series of activities planned out to elicit the support, encouragement, indulgence and optimum contribution of employees at all levels in an organization so as to bring about unceasing improvement towards the attainment of organizational goals.…”
Section: Literature Review Employees' Involvement In Decision Makingmentioning
confidence: 99%
“…Tizazu (2014) submits that employees' involvement can either be direct or indirect (advisory). In addition, Shaed et al (2018) indicated three mechanisms of EIDM to include (i) information sharing, (ii) consultative involvement, and (iii) democratic/delegative involvement. In the same vein, Asokk, Gudda, Bhati and Vanishree (2021) identified six ways through which management could involve employees.…”
Section: Forms Of Employees' Involvement In Decision Makingmentioning
confidence: 99%
“…Because businesses are composed of individuals, an escalating need exists to develop organizational change communication strategies emphasizing employee participation (Shin, Taylor and Seo, 2012). Nordin (2014) According to Shaed and Ishak et al (2015) employee participation is distribution of power between employer and employee in decision making process, either through direct or indirect involvement. Consequently, Malek et al (2012) emphasizes that participation is regarded as a key success factor during organizational change.…”
Section: Independent Variablesmentioning
confidence: 99%